Social Awareness Among Female Students at Princess Noura Bent Abdul Rahman University and The Role of The University in its Development (The International Journal of Educational Sciences and Arts, 2023)
This study aimed to identify the reality of social awareness among students of Princess Norah Bent Abdul Rahman University and the role of the university in its development. A descriptive survey method was used using a questionnaire, and a random sample of 600 female students was selected and an open question was asked to faculty members, where 10 members out of 100 answered.The results of the study showed that the reality of social awareness among the students of Princess Norah Bent Abdul Rahman University from the point of view of the students was average, and the results of the study showed that there were no differences in social awareness according to the type of the college variable.There were no differences due to the academic year variable showing that the role of the university in developing social awareness appeared through the unanimity of the sample members on 15 roles in it. The university plays a role in the development of social awareness in its students, as the frequency and proportion of this reinforcement have been used. The ratio ranged from (100% - 50%) and roles that were less than 50% were excluded.
Keywords: Social Awareness; Awareness Development; Social Skills; Noura University